Conceptual Model of E-Learning Flipped Classroom Based on Wasathiyyah Values: A New Paradigm for Preventing Digital Extremism among Islamic Religious Education Students - Mazidatun Ni'mah; Robby Rozaqiy; Moh Anas Ainul Hakim; Moch Hizam; Imam Syafi'i; Munawir (At Turots: Jurnal Pendidikan Islam, 2026)
ABSTRACT The increasingly massive spread of digital extremism among university students poses a serious challenge to Islamic Religious Education (PAI) learning in higher education. Thus far, PAI learning has heavily relied on conventional, teacher-centered approaches, while the utilization of Learning Management Systems (LMS) remains suboptimal. This study aims to formulate a Conceptual Model of E-Learning Flipped Classroom (ELFC) based on Wasathiyyah values as an effort to prevent digital extremism among PAI students. This study employs an exploratory qualitative approach using the library research method, and data analysis is conducted through qualitative content analysis of literature on educational technology and religious moderation. The results formulate a learning model that integrates four wasathiyyah values (Tawazun, I'tidal, Tasamuh, and Syura) into three learning phases: (1) Asynchronous Phase (Ta'aruf and Tafakkur); (2) Synchronous Phase (Mudzakarah and Syura); and (3) Post-Class Phase (Muhasabah and Aksi), which is the stage for self-evaluation and the production of counter-narratives on social media. This study indicates that the model encourages a shift in the lecturer's role from a material deliverer to a discussion facilitator, while simultaneously enhancing students' Higher-Order Thinking Skills in responding to contemporary religious issues. This conceptual model offers practical guidance for transforming the function of the campus LMS from a mere repository of teaching materials into a space that actively shields students from exposure to extreme ideologies.